Efficacy of Clopidrogel on Reperfusion and High-Sensitivity C-Reactive Protein in Patients with Acute Myocardial Infarction - Akbulut, Mehmet; Kutlu, Makbule; Ozbay, Yilmaz; Polat, Veli; Bilen, Mehmet Nail; Baydas, Adil; Altas, Yakup (Hindawi Ltd, 2009)
We investigated the effects of clopidogrel on reperfusion and inflammatory process in STEMI. A total of 175 STEMI patients with similar clinical characteristics were included to this study. One was the standard pharmacological reperfusion therapy group (group 1, n : 90), who received 300 mg aspirin, 70 U/kg bolus, and 12 U/kg/hr continuous infusion of unfractioned heparin and accelerated t-PA. Clopidogrel 450 mg loading and 75 mg/d thereafter was added to standard reperfusion therapy in the other group (group 2, n : 85). The ST-segment resolution, CK-MB, and high-sensitive CRP (hs-CRP) parameters were measured. Complete ST resolution was observed in 32 patients (36.8%) in group 1 and 53 patients (63.8%) in group 2 (P < .001). Also in the first 24 hours, the CK-MB levels of patients in group 1 were significantly higher than those of group 2 (P = .001). The hs-CRP values were greater in group 1 than group 2 at 48th hour (gruop 1: 9.4 +/- 0.1 mg/L, group 2: 3.7 +/- 1.4 mg/L; P = .000). We concluded that adding clopidogrel to standard treatment in STEMI patients provided early reperfusion and suppression of inflammatory response. Copyright (C) 2009 Mehmet Akbulut et al.
Keywords: Percutaneous Coronary Intervention; P-Selectin Expression; Clopidogrel Pretreatment; Aspirin; Fibrinolytics; Abciximab; Therapy; Cd40